Evaluation of the Public Health Center Management Information System (SIMPUS) in the City of Kediri - Denny Eka Putra; Sentot Imam Suprapto (Journal for Quality in Public Health, 2022)
Background It is necessary to evaluate the implementation of the Health Center Management Information System (SIMPUS). Concretely to improve the quality of service data results at the Puskesmas so that it can provide optimal service improvement results. The method used is descriptive analysis that uses qualitative research to identify the process of evaluating the implementation of the Puskesmas Management Information System (SIMPUS) with the Hot-Fit method approach.The results of the study identified aspects of the achievement of success for each element, namely, the human factor of achieving the target in terms of the intensity of SIMPUS implementation, mastery of HR, division of HR tasks and satisfaction that was above 50%, which means SIMPUS has been carried out but not maximized. In reporting the achievement of targets below 50% (10-20%) it means that there is a need for follow-up and improvement efforts in 9 Puskesmas. Organizational factors (organization) both in terms of structure, environment and training, the achievement of targets from 9 Puskesmas in Kediri City is more than 50%, it means SIMPUS has been implemented but has not been maximized. Technology (technology) factors are both system quality, information quality and service quality. The achievement of the target from 9 Puskesmas is more than 50%,which means SIMPUS has fulfilled all the elements but has not yet maximized the use of technology. Identification of the evaluation of aspects of the implementation of the Management Information System (SIMPUS) in accordance with the existing rules and procedures, but in its implementation it has not been carried out optimally.The conclusion is that the SIMPUS evaluation is one of the choices in decision making regarding the successful implementation of the Puskesmas Management Information System (SIMPUS) and the sustainability of the implementation of the Puskesmas Management Information System (SIMPUS).